ANALISIS PENGGUNAAN MEDIA SOSIAL DALAM MENGEMBANGKAN WAWASAN KEBANGSAAN PADA GENERASI MUDA TINGKAT REMAJA DI SMP SWASTA KRISTEN BNKP TELUKDALAM - Gaurifa, Yasita (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The aim of this research is to determine the use of social media in developing national insight in the younger generation at the teenage level at BNKP Telukdalam Christian Private Middle School for the 2023/2024 academic year. This type of research is descriptive qualitative research. The research results show that; 1) Social media is used to obtain information either directly or indirectly, talk via virtual or network, support success in learning, convey and receive messages, and 2) the development of national insight through the use of social media is to raise students' awareness to have a nationalist spirit, obey school rules and respect each other, students know the values ​​of Pancasila and Bhinneka Tunggal Ika as well as the importance of the interests and safety of the nation above personal or group interests, are aware of their duties as the next generation of the Indonesian nation, understand the importance of togetherness in achieving goals national level through serious learning, appreciating the services of heroes through participation in flag-raising ceremonies, realizing the importance of unity and integrity and understanding nationalism and patriotism. The suggestions put forward by researchers are: 1) Pancasila and citizenship education subject teachers should remind and instill the values ​​of national insight in students in every learning activity in class, 2) Students should use social media as well as possible in order to develop national insight in themselves. , and 3) Future researchers should be able to carry out more in-depth studies that are broadly relevant to this research.